Propofol suppresses LPS-induced nuclear accumulation of HIF-1α and tumor aggressiveness in non-small cell lung cancer - Yang, Nengli (Oncol Rep, 2017)
Tumor hypoxia has been recognized as a characteristic of the tumor microenvironment and promotes metastasis in a variety of types of cancer. However, in lung cancer, the role of hypoxia-inducible factor 1α (HIF-1α) in modulating the cellular response to the inflammation-related microenvironment remains unclear. In the present study, enhanced expression of HIF-1α accompanied by an increased ROS level was observed in lipopolysaccharide (LPS)-stimulated non-small cell lung cancer (NSCLC) cells. In addition, propofol, a general anesthetic, was found to significantly reduce the LPS-induced upregulation of HIF-1α and ROS in a dose-dependent manner. Further study showed that propofol may antagonize the role of LPS in activating HIF-1α through attenuating the protein stability and nuclear localization of HIF-1α. Moreover, knockdown of HIF-1α attenuated expression of mesenchymal marker, vimentin, but promoted the expression of epidermal marker, E-cadherin, in the LPS-treated NSCLC cells. Notably, LPS-induced epithelial-to-mesenchymal transition (EMT) was notably suppressed by propofol treatment. Consistently, a wound healing assay revealed that propofol abrogated LPS-stimulated migration of NSCLC cells while overexpression of HIF-1α reversed the effects of propofol. Similarly, we investigated the influence of propofol on the invasive capability of NSCLC cells. Western blot and RT-PCR analyses indicated that both knockdown of HIF-1α and treatment of propofol attenuated the LPS-activated expression of MMP2 and MMP9 which are necessary for tumor invasion. However, results from the Transwell assay confirmed that propofol also suppressed cell invasion by decreasing HIF-1α expression in the LPS-treated NSCLC cells. Analysis of clinical specimens demonstrated abnormal expression of HIF-1α in NSCLC tissues and a poor prognosis in patients with elevated HIF-1α expression. Thus, the present study suggests a potential strategy for NSCLC by targeting HIF-1α.